Mask-wearing behavior during COVID-19 in China and its correlation with e-health literacy - Zhang, Wei; Chen, Shu-Fan; Li, Kun-Kun; Liu, Huan; Shen, Hai-Chen; Zhang, Xian-Cui (Frontiers in Public Health, 2022)
Background: During the Coronavirus (COVID-19) pandemic, wearing masks became crucial for preventing infection risk and maintaining basic health. Therefore, it is necessary to understand the behavioral characteristics of the mask-wearing public to provide theoretical reference for the prevention and control of COVID-19. Methods: We conducted a nationwide survey on the mask-wearing behavior of the public and their health literacy levels by distributing electronic questionnaires. Univariate and logistic regression analyses were performed to determine the factors influencing mask-wearing behavior. Pearson’s correlation was used to analyze the correlation between mask-wearing behaviors and e-health literacy. Results: A total of 1972 valid questionnaires were collected; 99.8% of the public wore masks when going out and 59.2% showed good mask-wearing behavior. Most people choose to wear disposable medical masks (61.3%), followed by medical surgical masks (52.9%). All participants indicated that they had understood the information on how to use masks, and most obtained it through social media (61.8%). The e-health literacy scores of those with good mask-wearing behavior was an average of 29.72 (7.22), which is significantly higher than those with poor mask-wearing behavior 22.15(5.02, P<0.05), and each item score of the former’s e-health literacy was significantly higher than the latter (P<0.05). Further, there was a positive correlation between mask-wearing behavior and e-health literacy (R=0.550, P<0.05). Logistic regression analysis shows that seven factors are related to mask-wearing behavior, including gender, place of residence, educational level, work or living environment, marital status, flu symptoms, and whether living with people in home quarantine (P<0.01). Conclusion: The overall compliance of the public’s mask-wearing behavior in China during COVID-19 is good. However, there are shortcomings regarding the selection, use, and precautions. The differences in mask-wearing behavior are related to factors including gender, place of residence, educational level, work or living environment, marital status, presence of flu symptoms, and whether living with people in home quarantine. Higher levels of e-health literacy indicated better mask-wearing behavior. Therefore, it is necessary to strengthen the public’s popularization and education regarding the prevention and control of COVID-19.